Right heart failure in patient with resistant thyrotoxicosis due to Graves' disease - Volkanovska Ilijevska, Cvetanka; Tonovska, Irina (Bioscientifica, 2018)
Introduction: Resistant thyrotoxicosis is condition in which patients fail to respond to maximal doses of antithyroid drugs. Definitive treatment is radioactive ablation and operative treatment. However, achievement of euthyroid status before definitive treatment is important in patients with underlying cardiovascular disorder in whom thyroid crises can be detrimental. Case report: We describe a case of resistant thyrotoxicosis and right heart failure. A 55-year-old lady presented to our emergency center with complaints of chest pain, shortness of breath and distended stomach. On examination, she had blood pressure 140/80 mmHg, heart rate 40 bpm, jugular venous distension, pretibial edema, pansystolic murmur in the left paratsternal region and diffuse goitre. The abdomen was distended and the liver was palpable 2 cm below the right costal margin. The patient was diagnosed with Graves’ disease 15 days previously in another institution and had already started taking high doses of methimazole (60 mg) and propranolol (60 mg). Blood analysis confirmed a severe hyperthyroidism with a thyroid-stimulating hormone (TSH) <0.004 uIU/ml and elevated fT4–4.03 ngl/dl (N 0.90–1.80), fT3–9.94 pg/ml (N1.80–4.20) and normocytic anemia. Electrocardiogram showed bradicardic (40/min) sinus rhythm. Transthoracic echocardiography revealed a dilated right ventricle (52 mm) with a normal function and dimensions of left chambers. A severe tricuspid valve insufficiency was detected and estimated pulmonary artery systolic pressure was 60 mm Hg. The vena cava inferior was dilated and non-collapsing (24 mm). There was a mild mitral regurgitation grade III-IV. The methimazole was discontinued and treatment with maximum doses propylthiouracil (PTU) (300 mg three times a day), spironolacton and furosemid were initiated. The dose of propranolol was reduced (10 mg two times a day). After 2 weeks, fT4 and Ft3 were still significantly elevated and prednisolone (40 mg) was given in addition to the antithyroid drug. Four months later the patient clinically improved, but biochemical hyperthyroidism was still present. Definitive operative treatment was scheduled and in order to reduce the risk of precipitating thyroid crises the patient was given potassium iodide (150 mcg) in the next two weeks. Biochemical euthyroid state ensued and patient underwent total thyroidectomy. Thereafter tyroxine replacement therapy was started and pulmonary hypertension, atrial fibrillation and anemia resolved. Conclusion: Adjunctive drugs like prednisolone and potassium iodide play an important role in preparing patients with resistant thyreotoxisocis for more definitive treatment.
Keywords: thyreotoxisocis; right heart failure